Devlin - de Olievera, Paul; Roessler, Craig; Rosenthal, Rick (Lions Gate Home Entertainment, 1991)
Delvin is a New York Cop. an ex-alcoholic with a troubled past. When this estranged wife's brother, anti-crime mayoral candidate Jack Brennan is murdered, Devlin becomes the prime suspect. Set up by his father-in-law, one of the wealthiest, most powerful men in the city, Devlin, goes undercover to prove his innocence and clear his name. With the help of his girlfriend journalist, Eileen O'Malley, and his partner Sam Lord, Devlin uncovers a conspiracy that implicates the police force, a crime syndicate and the elder Brennan. This revelation leads Devlin into a showdown that explo-des into violence, bringing him face-to-face with painful memories from the past.